Coronary stent implantation in Behçet's disease - (:unkn) unknown (My University, 2002)
Behçet's disease (BD) is a systemic vasculitis that rarely involves the coronary arteries. Coronary arteritis may lead to myocardial infarction and death, and the management of coronary lesions due to BD has been described only in a small number of patients. The outcome of a young patient with BD is reported who was admitted with acute coronary syndrome and underwent balloon angioplasty and coronary stent implantation. Coronary stent implantation is an alternative treatment for coronary artery lesions of BD but careful monitoring is mandatory due to the progressive vasculities.
Keywords: Adult; Humans; Treatment Outcome; Behcet Syndrome; Male; Stents; Angioplasty, Balloon, Coronary; Coronary Stenosis